Qualitative evaluation of water origin and types of fertilizers used in vegetable cultivation in the Serra Geral region, Northern Minas Gerais - Ramos da Cruz, Sônia; Emanuel Cardoso Araújo, Vitor; Xavier Baliza, Patrícia; Vítor Brandão Leal, Paulo; Chaves Sicupira, Lázaro; Moreira Bittencourt Rigueira, Leila; Aparecida Guimarães Gusmão Gomes, Karla (Seven Editora, 2023)
Vegetables are a category of vegetables that includes vegetables grown in vegetable gardens, where parts such as roots, stems, leaves, flowers, fruits and seeds, are consumed by humans as food. Its consumption is extremely important for a healthy diet, because it has significant amounts of vitamins and minerals that, together with the medicinal properties that many have, help regulate and maintain the proper functioning of the body (MAKISHIMA et al., 2010). DOI: https://doi.org/10.56238/tfisdwv1-028